Social behaviour and sociability traits of dairy calves raised in a cow-calf contact system - Nabukalu, Maria Mwebaza (2021)
Calves are usually separated from their dams a few hours after birth, placed in individual house pens, cages or hutches and fed on milk replacer. This system has many welfare and ethical implications on the dam and calf, especially as regards to their bonding and natural behaviours. A case-control behavioural observational study was therefore carried out to evaluate the potential effects of early socialization of calves raised with their dams, other cows, and peers during the first months of life, on later social behaviour and sociability traits in dairy calves. We investigated this on 23 dairy calves that were born in the summer of 2019 and subjected them to two treatments: Cow-Calf Contact treatment (CCC) (10 dairy calves) and Control group (C) (13 dairy calves). When the CCC and the C calves were 25 and 22 weeks of age respectively, video recordings and social behaviours of the calves using focal scans and continuous behavioural observations were done for at least 6 hours/day for five days; three consecutive days when calves were in their groups, one day when the groups were mixed and a day after mixing the groups. A week later when the CCC and the C calves were 26 and 23 weeks old respectively, a runway test was done to evaluate the calves’ sociability. In addition, an avoidance distance test to evaluate animals’ fear towards humans and to quantify the human-animal relationship were also applied. The effect of Treatments (CCC and C), Sex (heifer and castrated male calves) and their interaction were analysed in response to the observed behaviours of calves as the dependent variables. Weaning weights of the calves were included in the model as covariates to social and locomotor play behaviours. Before mixing, castrated males were walking (F=5.76, P=0.028) and self-grooming (F=8.55, P=0.009) more than the heifers. CCC calves performed more bucking (F=5.91, P=0.026) and jumping (F=5.04, P=0.038) locomotor play behaviours than C calves. Social motivation to socialize was observed more in the CCC calves through initiating interactions by performing more pushing, butting and mock fighting play behaviours when mixed. CCC calves expressed a higher motivation to reunite at latency ˂60s and spent more time in the zone closer to the grouped calves compared to the C calves which could indicate a higher motivation to socialize. Potential sociality for both CCC and C calves in the presence of humans was tested through their docility with an attained mean avoidance or flight distance of 0.9m in both treatment groups. CCC calves chin pressed (F=7.40, P=0.022) more than the C calves during the feed competition test. Therefore, raising dairy calves in social contact with their dams, other cows and peers is most likely to positively influence the early development and performance of natural behaviours. Additionally, it could potentially influence the acquiring and retention of sociability traits in calves to positively interact with both familiar and unfamiliar mates, which in turn could ensure animal welfare and well-being at a later stage in life when dairy calves are grouped.